Antologi Puisi Dayita Karya Rosichin Mansur melalui Pendekatan Struktural : The Dayita Poetry Anthology by Rosichin Mansur: A Structural Approach - Haerani Haerani; Rosary Iriany; Imran Imran; Nuzul Tenriana; Andi Muhammad Nur (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to describe the physical structure and inner structure of women-themed poems in the poetry anthology Dayita by Rosichin Mansur. The research problem focuses on identifying the physical and inner structures contained in the poems and examining their relationship in constructing meaning. This study employed a descriptive qualitative method with a structural approach. The data consisted of words, phrases, lines, and stanzas containing elements of physical and inner structures in five poems, namely “Wanita”, “Ibu”, “Ibu 2”, “Adorasi Ibu”, and “Lembaran Jiwa”. Data were collected through reading and note-taking techniques, while data analysis used structural analysis by identifying typography, diction, imagery, concrete words, figurative language, rhyme and rhythm, as well as theme, feeling, tone, and message. The results show that the physical structure is formed through varied typography, emotive and religious diction, diverse imagery, concrete words clarifying meaning, figurative language enriching expression, and rhyme and rhythm creating musicality. The inner structure reveals themes of women’s dignity and maternal sacrifice with feelings of respect, affection, and emotion, an adoring tone, and messages emphasizing respect for women and appreciation of mothers. Therefore, the physical and inner structures are interconnected in constructing the overall meaning of the poems.